A cross sectional survey of 504 women regarding perceived risk factors and barriers to follow healthy lifestyle and association with sociodemographic factors and menopausal symptoms. Issue 6 (June 2022) - Chopra, Sakshi; Ranjan, Piyush; Verma, Aditi; Kumari, Archana; Malhotra, Anita; Upadhyay, Ashish Datt; Baitha, Upendra; Vikram, Naval K.
Abstract: Background and aims: Midlife women undergoing menopausal transition are predisposed to weight gain. Weight gain in midlife is driven by two modifiable risk factors: menopausal symptom's severity and lifestyle practices. The independent and interactive nature of menopausal symptoms and lifestyle practices as risk factors of weight gain has not been investigated yet. This study was undertaken to study menopausal symptoms and lifestyle practices as risk factors for weight gain in midlife women and identify midlife -related barriers in managing corrective lifestyle practices. Methods: In this cross-sectional study, menopausal symptom severity and lifestyle practices such as diet, exercise, and sleep were assessed using a pre-validated and reliable questionnaire on a convenience sample of midlife women (43–55 years) via an interview schedule. The association of lifestyle practices and its barriers with socio-demographics and menopausal symptoms were analysed. Result: A total of 504 women (mean age: 47.3 ± 4.1 years) were recruited. More than half of them followed corrective dietary practices, but only one-fourth engaged in moderate-intensity exercises. Total menopausal symptom severity was associated with increased food intake (P < 0.001), joint pain with limited physical activity and hot flashes and emotional volatility with sleep disturbances (P < 0.01). Demographic variables such as education, economic and employment status were associated with unhealthy lifestyle practices. Conclusion: Assessment of menopausal symptoms and lifestyle practices as risk factors and associated barriers must be the pivotal component to devise comprehensive women-centric weight management modules. Similar studies should be carried out in future when there is no clear effect of COVID19 on lifestyle factors. Highlights: Discordance between the self-perceived and actual weight status in midlife women was found. Musculoskeletal disability was the primary cause for limited physical activity. Hot flushes and emotional volatility led to sleep disturbances during menopausal transition. Higher education and economic status were associated with consumption of energy dense foods and limited physical activity. Similar studies should be repeated in the future when the impact of COVID-19 is less prevalent amongst midlife women.